2013
DOI: 10.1093/jb/mvt019
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide-insensitive quinol oxidase (CIO) from Gluconobacter oxydans is a unique terminal oxidase subfamily of cytochrome bd

Abstract: Cyanide-insensitive terminal quinol oxidase (CIO) is a subfamily of cytochrome bd present in bacterial respiratory chain. We purified CIO from the Gluconobacter oxydans membranes and characterized its properties. The air-oxidized CIO showed some or weak peaks of reduced haemes b and of oxygenated and ferric haeme d, differing from cytochrome bd. CO- and NO-binding difference spectra suggested that haeme d serves as the ligand-binding site of CIO. Notably, the purified CIO showed an extraordinary high ubiquinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…The amino acid sequences of the two subunits of CIO, CioA and CioB, are highly similar to those of the canonical bd oxidases CydA and CydB, respectively, but the conserved sequence of the periplasmic loop (Q loop) that contains the putative quinol-oxidizing site is significantly shorter in CioA than in CydA (9). CIO of P. aeruginosa was predicted to have high affinity for oxygen, but its K m value for oxygen determined in this study was comparable to those of aa 3 and Cyo, indicating that it is a low-affinity enzyme, similar to the CIOs of C. jejuni and G. oxydans (Table 2) (13,14). The low affinity of CIOs for oxygen is in contrast to the high affinity of the canonical bd oxidase of E. coli (42,43).…”
Section: Figmentioning
confidence: 76%
See 4 more Smart Citations
“…The amino acid sequences of the two subunits of CIO, CioA and CioB, are highly similar to those of the canonical bd oxidases CydA and CydB, respectively, but the conserved sequence of the periplasmic loop (Q loop) that contains the putative quinol-oxidizing site is significantly shorter in CioA than in CydA (9). CIO of P. aeruginosa was predicted to have high affinity for oxygen, but its K m value for oxygen determined in this study was comparable to those of aa 3 and Cyo, indicating that it is a low-affinity enzyme, similar to the CIOs of C. jejuni and G. oxydans (Table 2) (13,14). The low affinity of CIOs for oxygen is in contrast to the high affinity of the canonical bd oxidase of E. coli (42,43).…”
Section: Figmentioning
confidence: 76%
“…1B) clearly showed that P. aeruginosa CIO is a low-affinity enzyme, similar to the CIOs of C. jejuni and G. oxydans (13,14). The low affinity of these CIOs is in contrast to the high affinity of the canonical bd oxidase of E. coli (42).…”
Section: Five Terminal Oxidases Of P Aeruginosamentioning
confidence: 98%
See 3 more Smart Citations